Existence of Crystalline Ammonium Sulfate Nuclei Affects Chemical Reactivity of Oleic Acid Particles Through Heterogeneous Nucleation - Liu, W.; Liao, K.; Q. Chen; He, L.; Y. Liu; Kuwata, M. (Journal of Geophysical Research: Atmospheres, 2023)
Organic aerosol particles are oxidized by atmospheric oxidants. These particles are occasionally internally mixed with solid materials such as soot and inorganic crystals. However, potential impacts of the particles' mixing states on chemical reactivity have rarely been investigated. This study investigated the influence of the existence of crystalline ammonium sulfate on chemical reactivity of oleic acid particles with ozone for the temperature range of −20°C to +35°C using an aerosol flow tube reactor. The chemical compositions of the resulting particles were monitored using online instruments for deriving the reactive uptake coefficients (γ) of ozone by oleic acid. The values of γ were not significantly influenced by the existence of ammonium sulfate when the temperature of the reactor was higher than the melting point of oleic acid (∼13°C). The values of γ were unmeasurably small for the lower temperature range when oleic acid particles were internally mixed with crystalline ammonium sulfate. No significant change in γ was observed for the temperature range down to −13°C when the inorganic salt was absent, likely due to the formation of supercooled liquid. The difference in chemical reactivity can be explained by the occurrence of heterogeneous nucleation induced by inorganic seed.